UGC NET CS 2007 JunePaper2
October 13, 2023DigitalLogicDesign
October 13, 2023UGC NET CS 2007 JunePaper2
Question 9

If A⊕B=C , then :
A ⊕ C = B


B ⊕ C = A


A ⊕ B ⊕ C = 1


A ⊕ B ⊕ C = 0


None of the above

Question 9 Explanation:
Given that A⊕B=C
1) A⊕B⊕ C = C⊕C
A⊕B⊕ C = 0 (Since C⊕C =0)
option D is correct.
So option C is not correct.
2) From step 1, we know that A⊕B⊕ C = 0
A⊕B⊕ C ⊕ B= 0 ⊕ B
A ⊕ C = B (Since B ⊕ B= 0)
So option A is correct.
3) From step 1, we know that A⊕B⊕ C = 0
A⊕B⊕ C ⊕ A= 0 ⊕ A
B ⊕ C = A (Since A ⊕ A =0)
So option B is also correct.
1) A⊕B⊕ C = C⊕C
A⊕B⊕ C = 0 (Since C⊕C =0)
option D is correct.
So option C is not correct.
2) From step 1, we know that A⊕B⊕ C = 0
A⊕B⊕ C ⊕ B= 0 ⊕ B
A ⊕ C = B (Since B ⊕ B= 0)
So option A is correct.
3) From step 1, we know that A⊕B⊕ C = 0
A⊕B⊕ C ⊕ A= 0 ⊕ A
B ⊕ C = A (Since A ⊕ A =0)
So option B is also correct.
Correct Answer: E
Question 9 Explanation:
Given that A⊕B=C
1) A⊕B⊕ C = C⊕C
A⊕B⊕ C = 0 (Since C⊕C =0)
option D is correct.
So option C is not correct.
2) From step 1, we know that A⊕B⊕ C = 0
A⊕B⊕ C ⊕ B= 0 ⊕ B
A ⊕ C = B (Since B ⊕ B= 0)
So option A is correct.
3) From step 1, we know that A⊕B⊕ C = 0
A⊕B⊕ C ⊕ A= 0 ⊕ A
B ⊕ C = A (Since A ⊕ A =0)
So option B is also correct.
1) A⊕B⊕ C = C⊕C
A⊕B⊕ C = 0 (Since C⊕C =0)
option D is correct.
So option C is not correct.
2) From step 1, we know that A⊕B⊕ C = 0
A⊕B⊕ C ⊕ B= 0 ⊕ B
A ⊕ C = B (Since B ⊕ B= 0)
So option A is correct.
3) From step 1, we know that A⊕B⊕ C = 0
A⊕B⊕ C ⊕ A= 0 ⊕ A
B ⊕ C = A (Since A ⊕ A =0)
So option B is also correct.
Subscribe
Login
0 Comments